Butyrate-producing human gut symbiont, Clostridium butyricum, and its role in health and disease. (1st January 2021) - Stoeva, Magdalena K.; Garcia-So, Jeewon; Justice, Nicholas; Myers, Julia; Tyagi, Surabhi; Nemchek, Madeleine; McMurdie, Paul J.; Kolterman, Orville; Eid, John
ABSTRACT: Clostridium butyricum is a butyrate-producing human gut symbiont that has been safely used as a probiotic for decades. C. butyricum strains have been investigated for potential protective or ameliorative effects in a wide range of human diseases, including gut-acquired infection, intestinal injury, irritable bowel syndrome, inflammatory bowel disease, neurodegenerative disease, metabolic disease, and colorectal cancer. In this review we summarize the studies on C. butyricum supplementation with special attention to proposed mechanisms for the associated health benefits and the supporting experimental evidence. These mechanisms center on molecular signals (especially butyrate) as well as immunological signals in the digestive system that cascade well beyond the gut to the liver, adipose tissue, brain, and more. The safety of probiotic C. butyricum strains appears well-established. We identify areas where additional human randomized controlled trials would provide valuable further data related to the strains' utility as an intervention.